Meta-analysis of substitution value of maize with cassava (Manihot esculenta Cratnz) on growth performance of broiler chickens - Ogbuewu, Ifeanyichukwu Princewill; Mbajiorgu, Christian Anayo (Frontiers in Veterinary Science, 2022)
There are variable results on the effect of cassava on the performance characteristics of broiler chickens. As a result, this meta-analysis was performed to determine the effect of cassava on feed intake, feed conversion ratio (FCR), and average daily gain (ADG) in broiler chickens. A methodical search performed on Google Scholar, Scopus, Web of Science, and PubMed databases as well as individual journals yielded 365 published articles. Out of 365 studies, 23 that met the inclusion criteria were used for the meta-analysis. Outcome measures were pooled using a random-effects model. Results were expressed as standardized mean differences (SMD) at 95% confidence intervals (CIs). Subgroup and meta-regression analyses were used to explore the effects of studied covariates (broiler strain, inclusion level of cassava, number of broilers per replicate, cassava processing methods, and cassava form) on measured outcomes. Results indicated that cassava had a small positive effect on feed intake (SMD = −0.07, 95% CI −0.26, 0.12) and FCR (SMD = 0.14; 95% CI 0.82, 1.746), but a large negative effect on ADG (SMD = −1.67; 95% CI −1.99, −1.35) compared to the controls. Subgroup analysis by cassava form showed that wet fermented cassava peel meal (WFCPM) had a moderate impact on feed intake (SMD = 0.62, 95% CI 0.47, 0.77) and ADG (SMD = 0.66, 95% CI 0.37, 0.95) in broiler chickens compared with the controls. Our results also found improved growth performance in broiler chickens fed cassava at 4–10%. There is evidence of between-study variance, and studied covariates explain most of the sources of heterogeneity. This study concluded that the replacement of maize with 4–10% WFCPM improved growth performance traits in broiler chickens.